Factors associated with septic arthritis of the distal interphalangeal joint in beef cattle: A case-control study. (February 2019) - Chamorro, M.F.; Reppert, E.J.; Robinson, L.; Cernicchiaro, N.; Biller, D.; Miesner, M.
Highlights: The duration of lameness was not associated with diagnosis of septic arthritis of the distal interphalangeal joint (DIJ). The presence of a lameness score of ≥4 increased the probability of septic arthritis of the DIJ by 85.7%. The presence of asymmetric swelling at the coronary band was closely associated with septic arthritis of the DIJ. Abstract: Lameness in cattle is a welfare concern and is associated with important economic losses in beef cattle operations. Infection of the distal interphalangeal joint (DIJ) results in severe lameness and if left untreated carries a poor prognosis. Diagnosis of DIJ infection is challenging in the field. The aim of this study was to determine factors associated with septic arthritis of the DIJ in beef cattle. Thirty-nine beef cattle with a complaint of single-foot lameness were used in this study. History and lameness examination data were recorded and analyzed. Radiographic changes and cytology of synovial fluid of the affected DIJ were used to define the presence (cases) or absence (controls) of DIJ infection. Asymmetric swelling at the coronary band of the affected foot and a lameness score of ≥4/5 significantly increased the odds (odds ratio [OR] = 63.2 and OR = 120, respectively) of diagnosis of septic arthritis of the DIJ in beef cattle with a single-foot lameness compared to cattle with no asymmetry of the coronary band or lameness scores <3. Routine lameness examination findings could be used in the field to rapidly recognize infection of the DIJ in lame beef cattle.